High Andean butterflies from southern Peru, I. Dry puna Satyrinae, with the description of two new taxa and three new records from Peru (Lepidoptera: Nymphalidae) - Cerdeña, José Alfredo (2014)
This is the first part of a series of contributions to the knowledge of the high Andean butterfly fauna in southern Peru. In this work the butterfly species of the subfamily Satyrinae present in the dry puna of Peru are reviewed. A new species, Pampasatyrus gorkyi sp. nov. and a new subspecies Argyrophorus lamna cuzcoensis ssp. nov. are described from the department Cusco, Peru. Three species are recorded for the first time for Peru, Argyrophorus gustavi Staudinger, Faunula euripides (Weymer) and Faunula eleates (Weymer) previously reported from Chile and Bolivia. Ecological and biogeographical data are provided.